What Are the Options for the Treatment of Stuttering in Preschool Children? - Shenker, Rosalee C.; Santayana, Gissella (Seminars in Speech and Language, 2018)
Treatment of stuttering during the preschool years is considered to be the best prevention of persistent chronic stuttering; however, many clinicians do not feel comfortable treating stuttering and may be confused about choosing an intervention. This article summarizes the history of direct and indirect methodology for treatment of stuttering in preschool children. It provides an update of contemporary treatments and discusses issues related to the timing of treatment. Guidelines for choosing a level of treatment based on the risk of a preschool child continuing to stutter are discussed, with examples of which children would be most appropriate for which level of intervention.
Keywords: Stuttering treatment; preschool children; guidelines